Tailoring ISO/IEC/IEEE 29119-3 standard for small and medium-sized enterprises - Eira, Paulo (2018)
IT companies tend to overlook software development processes, and, consequently, end up following poorly defined or inconsistent software development and testing process, in part due to their associated high costs, complexity and extensiveness of some of these processes and associated standards. In addition, according to our experience, these organizations show severe difficulties when attempting to follow and apply existing standards related to regulation and software testing processes, as is the case of the ISO 29119-3 standard. Therefore, this paper discusses the applicability of this ISO 29119-3 standard in Small and Medium-size Enterprises (SMEs), by presenting an iterative and interactive process for tailoring. The goal is to satisfy the testing process needs of these SMEs, combining the software development process with key points of the ISO 29119-3 standard, without infringing its integrity. The tailoring process is then applied and discussed in a live setting. Such results showed improvements in an SME testing process, using the tailored ISO 29119-3 as a guideline, minimizing considerable amounts of resources.